O pochodzeniu narodów. Między prymordializmem a modernizmem - Migalski, Marek (Political Preferences, 2017)
On the Origin of Nations. Between primordialism and modernism The essay concerns issue of origin of the nations. Author presents discussion about when nations were „discovered”. The main topic is dedicated dispute between main scientific approaches represented by primordialism, modernism, ethnosymbolism and perenialism. Author presents all of them and in the conlusions takes a stand in this discussion as a moderate modernist, who accepts some ideas of ethnosymbolism. Key words: nation, primordialism, modernism, ethnosymbolism